2008
DOI: 10.1007/s11240-008-9410-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of neural networks for prediction of in vitro culture conditions and inoculum properties for optimum productivity

Abstract: This study represents an ANN based computational scheming of physical, chemical and biological parameters at flask level for mass multiplication of plants through micropropagation using bioreactors of larger volumes. The optimal culture environment at small scale for Glycyrrhiza plant was predicted by using neural network approach in terms of pH and volume of growth medium per culture flask, incubation room temperature and month of inoculation along with inoculum properties in terms of inoculum size, fresh wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…ANN technology has been found to be completely applicable for experiments with different numbers of data points, which makes it possible to use more casual experimental designs than is allowed with statistical approaches (Ahmadi and Golian, 2011). Recently, several studies have demonstrated the effectiveness of ANNs in the field of plant tissue culture for different purposes such as predicting the number of shoots per explant and average shoot length (Gago et al, 2010a, 2011; Nezami Alanagh et al, 2014), modeling the weight of root biomass (Mehrotra et al, 2008, 2013; Prakash et al, 2010), and predicting the number of roots per microshoots and survival percentage (Gago et al, 2010a,b). ANN-GA is a hybrid technology that combines the adaptive learning capabilities from ANN with a GA.…”
Section: Introductionmentioning
confidence: 99%
“…ANN technology has been found to be completely applicable for experiments with different numbers of data points, which makes it possible to use more casual experimental designs than is allowed with statistical approaches (Ahmadi and Golian, 2011). Recently, several studies have demonstrated the effectiveness of ANNs in the field of plant tissue culture for different purposes such as predicting the number of shoots per explant and average shoot length (Gago et al, 2010a, 2011; Nezami Alanagh et al, 2014), modeling the weight of root biomass (Mehrotra et al, 2008, 2013; Prakash et al, 2010), and predicting the number of roots per microshoots and survival percentage (Gago et al, 2010a,b). ANN-GA is a hybrid technology that combines the adaptive learning capabilities from ANN with a GA.…”
Section: Introductionmentioning
confidence: 99%
“…However, culture of these hairy roots for high secondary metabolite associated with better biomass production requires optimization of several physical and chemical parameters that affect the growth and productivity of these roots. A feed-forward back-propagation neural network model was developed (Mehrotra et al 2008) for prediction of in vitro culture conditions for hairy root growth. The model used inoculum size, fresh weight, density, culture temperature, pH, and time of inoculation as input parameters and final fresh weight of roots as final parameters.…”
Section: Applications Of Artificial Neural Network In Plant Biologymentioning
confidence: 99%
“…Successful attempts at modeling in vitro culture parameters have also been made in the hairy root cultures of Glycyrrhiza glabra (Mehrotra et al, 2008;Prakash et al, 2010). Initially, the prediction model of in vitro culture conditions was designed along with the inoculum properties for optimum root biomass production (Mehrotra et al, 2008). This model consisted of an MLP performed in Matlab software.…”
Section: Predicting Optimal Conditions For In Vitro Culturementioning
confidence: 99%